PENGARUH SISTEM PENILAIAN KINERJA DAN INTELLECTUAL CAPITAL TERHADAP EFEKTIVITAS IMPLEMENTASI TOTAL PERFORMANCE SCORECARD DAN IMPLIKASINYA DALAM MENINGKATKAN KUALITAS JASA (Studi Pada Perbankan Syari’ah di Pulau Jawa) - Maghfiroh, Siti; Sutanto, Intan Imam (BISNIS, 2013)
Improvement of service quality for banking institutions is one of the key factorsin the competition international in this globalization era Total PerformanceScorecard (TPS) is an approach to improvement the quality continually fromevery business aspect and organization totality. In its application, TPSimplementation is affect another factors that is: intellectual capital andperformance appraisal performance to increase service quality and performanceof higher education. The purpose of this research are analyze and verify theeffect of performance appraisal system and intellectual capital toward totalperformance scorecard and their implication of toward service quality at Islamicbanking in Indonesia. The type of this research is descriptive and verification,while the method used both descriptive and verification survey. The data will beanalyzed by using descriptive analysis, simple regression and multipleregression. The results indicate that: 1) performance appraisal system andintellectual capital have significant effect toward implementation of totalperformance scorecard, 2) implementation of total performance scorecard havesignificant effect toward service quality at Islamic banking in Java,